Analisis Pemborosan (Waste) Pada Aktivitas Inbound Bulky Warehouse Menggunakan Metode Value Stream Mapping (VSM) Dan Fishbone - Virdania, Rayna; Trihastari, Ulin; Kania, Dinar Dewi (Jurnal Sistem Transportasi & Logistik, 2024)
Company X, which operates in the e-commerce sector, provides end-to-end logistics services, including supply chain management, distribution, transportation, and storage. Currently, the company faces challenges in achieving inbound KPI targets due to a lack of communication regarding standard operating procedures (SOPs), resulting in slow and time-consuming inbound processes. This study aims to analyze the entire inbound process at Company X’s bulky warehouse using Lean Warehousing and Value Stream Mapping (VSM) techniques. The findings show improvements in time efficiency, with Value Added (VA) time decreasing from 210 minutes to 165 minutes, Non-Value Added (NVA) time reduced from 135 minutes to 25 minutes, and Necessary Non-Value Added (NNVA) time reduced from 105 minutes to 50 minutes after implementing VSM. By applying VSM and improvements using streamlining tools, Company X successfully enhanced time efficiency and reduced waste in the inbound process.